Efficacy of intramuscular clodronate in Complex Regional PainSyndrome type I: description of a case located in the astragalus in apatient with psoriatic arthritis - Cassisi, G.; Sartori, L. (Acta Biomedica Atenei Parmensis, 2009)
Reflex sympathetic dystrophy or Complex Regional Pain Syndrome type I (CRPS I) is a painful regional disease with non-metameric topography, which shows extreme pathomorphological variability, from forms in which pain is the only clinical manifestation, to “pseudo-purulent” forms characterized by impressive local manifestations. The use of high doses of bisphosphonates in the treatment of CRPS I is confirmed in different publications which associate their efficacy with their specific biological properties and multiple actions at local level. This case report describes a case of CRPS I in the astragalus of a patient with psoriatic arthritis, successfully treated with intramuscular clodronate.